AN INFLUENCE OF INTEREST RATE, FINANCIAL LITERACY AND QUALITY SERVICE ON CUSTOMER DECISION TO SAVING AT PT BANK SUMUT BRANCH PEMATANG RAYA SIMALUNGUN - Desy Astrid Anindya (Jurnal Ekonomi, 2023)
The purpose of this study was to determine the effect of interest rates, financial literacy and service quality on customer decisions to save at PT Bank Sumut Pematang Raya Simalungun Branch. The types of data used in this study are quantitative data, using primary data sources. The data collection method used a questionnaire. The population in this research is a customer of Bank Sumut, Pematang Raya Simalungun Branch who uses the Martabe savings type in 2020 and 2021 as much as 33,271 people. Quality service has a positive effect on customer decisions to save at the bank North Sumatra Simalungun Branch Pematang Raya. Simultaneously the interest rate, financial literacy, and service quality have a positive effect on customer decisions save at PT Bank Sumut Pematang Raya Simalungun Branch. Quality service has a positive effect on customer decisions to save at the bank North Sumatra Simalungun Branch Pematang Raya. Simultaneously the interest rate, financial literacy, and service quality have a positive effect on customer decisions save at PT Bank Sumut Pematang Raya Simalungun Branch.